El cuento estrategia pedagógica de las habilidades comunicativas de grado segundo (2017)
The present work is the documentation of the pedagogical practice experienced in three instances, the first diagnosis, the second implementation of pedagogical strategies in the face of what is identified and ultimately the systematization that gives birth to what is here recorded, the chosen course was first, but since time does not stop they went to second, At that time, an investigation of middle childhood and the first cycle of education was carried out finding that the students had difficulties when expressing themselves, in addition to In improvisation games they did not tell a story with a narrative structure, which made that the question was born of how to develop narrative thinking at these ages, and the The answer that was found was that this thought arises when boys and girls develop communication skills, then it was investigated, and it was found that the first contact of the human being with the world is with listening from the mother's womb, then They learn to speak, imitating their relatives, the skills of reading and writing are develop in the school in this case the Colombo Florida Bilingual School, with which a contextualization of the students through the survey that reported that they are class medium, who has a person who helps them at home and who, because he is bilingual, They dedicated a large number of hours to language skills.